2019
DOI: 10.1021/acsbiomaterials.8b01554
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Changes of Mechanical Microenvironment in Skin Wounds During Negative Pressure Wound Therapy

Abstract: Cell migration, proliferation, and differentiation are regulated by mechanical cues during skin wound healing. Negative pressure wound therapy (NPWT) reduces the healing period by optimizing the mechanical microenvironment of the wound bed. Under NPWT, it remains elusive how the mechanical microenvironment (e.g., stiffness, strain gradients) changes both in time and space during wound healing. To illustrate this, the healing time of full-thickness skin wounds under NPWT, with pressure settings ranging from −50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The results from the present animal study specifically showed that the mean maximum force to skin failure, the UTS and the structural stiffness were all mildly greater for skin at and near the incisions treated by means of the CB‐125 suNPWT system (Figure 8E). Of note, Chen and colleagues 49 recently used shear wave elastography to demonstrate that in a rabbit model, the stiffness of wounded skin increases during NPWT‐supported healing; however, the rise in the stiffness of the repaired skin depends on the NPWT protocol, and, specifically, on the level of the delivered negative pressure. The extent of skin stiffness changes in their work appeared to be more sensitive to the magnitude of the delivered negative pressure nearer the time of infliction of the surgical wound; after 1 day, negative pressure levels of −125 or −150 mmHg led to mildly greater elastic moduli of the wounded skin than negative pressures of −50 or −80 mmHg 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present animal study specifically showed that the mean maximum force to skin failure, the UTS and the structural stiffness were all mildly greater for skin at and near the incisions treated by means of the CB‐125 suNPWT system (Figure 8E). Of note, Chen and colleagues 49 recently used shear wave elastography to demonstrate that in a rabbit model, the stiffness of wounded skin increases during NPWT‐supported healing; however, the rise in the stiffness of the repaired skin depends on the NPWT protocol, and, specifically, on the level of the delivered negative pressure. The extent of skin stiffness changes in their work appeared to be more sensitive to the magnitude of the delivered negative pressure nearer the time of infliction of the surgical wound; after 1 day, negative pressure levels of −125 or −150 mmHg led to mildly greater elastic moduli of the wounded skin than negative pressures of −50 or −80 mmHg 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding and correctly predicting the mechanical properties of human skin are essential for medical applications. Planning of reconstructive surgery (Mollemans et al 2007;Beldie et al 2010;Lee et al 2018), wound healing (Buganza Tepole and Kuhl 2016; Evans et al 2013; Barnes et al 2018;Chen et al 2019) and growth through "expanders" (Zöllner et al 2012(Zöllner et al , 2013Buganza Tepole et al 2011) depend on deformations as well as the force distribution within the skin. Investigating and unveiling the underlying mechanical and mechanobiological processes require accurate models of the skin's response under diverse conditions of mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, the negative pressure wound therapy (NPWT) technology is used to absorb wound exudates and relieve edema, which may result in accelerate wound healing. [ 9 ] However, improper negative pressure may lead to the inhibition of perioperative blood flow, making the wound more difficult to heal. Furthermore, NPWT requires an electronic device and needs to be combined with other wound dressing materials for successful therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its hydrophobicity, it is difficult to quickly absorb exudate, so it is necessary to apply together with the negative pressure wound therapy (NPWT) technology for treatment. [ 9 ] Nonetheless, improper negative pressure will not only make the patient feel strong pain, but also cause secondary problems such as blood flow inhibition and tension blisters around the wound. [ 10 ] Therefore, it is a clinical need to develop simple wound dressings with high capacity to absorb large amounts of exudate rapidly.…”
Section: Introductionmentioning
confidence: 99%